Treatment Outcome and Associated Factors of Neonatal Sepsis at Mizan Tepi University Teaching Hospital, South West Ethiopia: A Prospective Observational Study - Wale A; Chelkeba L; Wobie Y; Abebe A (Dove Medical Press, 2021)
Alemnew Wale,1 Legese Chelkeba,2 Yohannes Wobie,3 Abinet Abebe3 1Clinical Midwifery, Department of Midwifery, College of Medicine and Health Science, MizanTepi University, Mizan, Ethiopia; 2Clinical Pharmacy, School of Pharmacy, Institute of Health, Addis Ababa University, Addis Ababa, Ethiopia; 3Clinical Pharmacy, School of Pharmacy, College of Medicine and Health Science, MizanTepi University, Mizan, EthiopiaCorrespondence: Alemnew Wale; Yohannes Wobie Email walealemnew@gmail.com; yohanneswobie@gmail.comIntroduction: Neonatal sepsis is the gravest problem in neonates, ending in significant morbidity and mortality. World wide 6.9 million neonates were spotted with potentially severe bacterial infections needing treatment and 2.6 million of them occurred in sub-Saharan Africa (SSA). Sepsis is the leading cause of neonatal mortality and is perhaps answerable for about 30- 50% of the total neonatal deaths per year in emerging countries.Objective: This study aims to assess the treatment outcome and associated factors of neonatal sepsis at Mizan Tepi University Teaching Hospital, South West Ethiopia.Methods: A hospital-based prospective observational study was done at Mizan Tepi University Teaching Hospital (MTUTH) from May to November 2019 among neonates admitted with sepsis. Data were entered to Epi-data 4.2 and analyzed by SPSS version 21. Bivariate and multivariate Cox regression was used to identify the relationship between dependent and independent variables. All neonates ≤ 28 days who were admitted to MTUTH at the neonatal intensive care unit (NICU) and neonates diagnosed with sepsis by the attending physician either clinically or laboratory-confirmed included in the study.Results: Of the 211 neonatal sepsis patients, 110 (52.1%) were females, 161 (76.3%) were admitted with late-onset sepsis, 16 (7.6%) were very low birth weight, and 156 (73.9%) were term. About 143 (67.8%) had a good outcome and 68 (32.2%) had a poor outcome. Very low birth weight [P = 0.006, AHR = 1.692, 95% CI: (1.245, 4.36)], age of neonate being less than 4 days at admission [P = 0.001, AHR = 9.67, 95% CI: (2.24, 41.70)], maternal infection [P = 0.032, AHR = 3.186, 95% CI: (1.32, 30.68)], and prolonged length of hospital stay [(P = 0.017, AHR = 12.29, 95% CI: (1.55, 96.31), were significantly associated to mortality.Conclusion: The mortality rate of neonatal sepsis was found to be high. Age of neonate < 4 days, birth weight of the neonate < 1500 gm, and prolonged length of hospital stay were identified as independently associated factors of increased risk of mortality.Keywords: neonate, sepsis, treatment outcome, Mizan, Ethiopia 2021